Shengjiang Xiexin Decoction Alters Pharmacokinetics of Irinotecan by Regulating Metabolic Enzymes and Transporters: A Multi-Target Therapy for Alleviating the Gastrointestinal Toxicity - Guan, Huan-yu; Li, Peng-fei; Wang, Xiao-ming; Yue, Jia-jing; He, Yang; Luo, Xiao-mei; Su, Mei-feng; Liao, Shang-gao; Shi, Yue (Frontiers in Pharmacology, 2017)
Shengjiang Xiexin decoction (SXD), a classic traditional Chinese medical formula chronicled in Shang Han Lun, is used in modern clinical practice to decrease gastrointestinal toxicity induced by the chemotherapeutic drug irinotecan (CPT-11). In this study, the effect of SXD on the pharmacokinetics of CPT-11 and its active metabolites (SN-38 and SN-38G), and the underlying mechanisms were further examined. An ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) method was developed and validated for the simultaneous quantification of CPT-11, SN-38 and SN-38G in the plasma, bile, liver, intestine and intestinal contents of control and SXD-pre-treated rats after intravenous administration of CPT-11. SXD pretreatment increased the area under the curve (AUC) and the initial plasma concentration (C0) of CPT-11 but decreased the plasma clearance (CL). The AUC and the maximum plasma concentration (Cmax) of SN-38 decreased, whereas the Cmax of SN-38G increased. Compared with that of the control group, the biliary excretion of CPT-11, SN-38 and SN-38G was inhibited. The CPT-11, SN-38 and SN-38G concentrations in the liver, intestine and intestinal contents were different between the two groups. Furthermore, the hepatic expression of multidrug resistance-associated protein-2 (Mrp-2), P-glycoprotein (P-gp) and carboxylesterase 2 (CES2) was significantly down-regulated by SXD, while the hepatic and jejunal uridine diphosphate (UDP)-glucuronosyltransferase 1A1 (UGT1A1) expression was elevated. The hydrolysis of CPT-11 to SN-38 by CES and the glucuronidation of SN-38 to SN-38G by UGT were affected by liver and jejunum S9 fractions from rats pre-treated with SXD. Therefore, this study demonstrated for the first time that SXD could alter the pharmacokinetics of CPT-11 and its metabolites to alleviate CPT-11-induced diarrhea. And the underlying mechanism of drug interaction between CPT-11 and SXD involves decreasing hepatic Mrp-2 and P-gp expression and altering the activities of CES and UGT.